2005
DOI: 10.1177/1721727x0500300301
|View full text |Cite
|
Sign up to set email alerts
|

Could Chlamydia Pneumoniae Be Considered an Infectious Risk Factor for Inflammatory Diseases Such as Atherosclerosis ?

Abstract: Chlamydia pneumoniae, a Gram-negative intracellular obligate bacteria, is recognised as a common cause of upper respiratory tract infections, and accounts for ∼10% of community-acquired pneumonia. In recent years, chronic and persistent infection with C. pneumoniae has been implicated in the pathogenesis of atherosclerosis. Atherosclerosis is regarded as a chronic inflammatory disease that results from complex interactions between a variety of cell types such as endothelial cells, vascular smooth muscle cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…1 Periods when students were present were not compared statistically with unoccupied periods. Sessa et al 11 found that occupancy in a university auditorium (180 students), as well as in an office (18 m 2 , four individuals), and an apartment (110 m 2 , two individuals), was associated with a 2-4-fold increase in the concentration of airborne, culturable bacteria. A study of indoor air quality parameters in a lecture theatre in a Singapore school offers additional indirect evidence that the presence of occupants in classrooms may result in higher levels of bioaerosols.…”
Section: Introductionmentioning
confidence: 99%
“…1 Periods when students were present were not compared statistically with unoccupied periods. Sessa et al 11 found that occupancy in a university auditorium (180 students), as well as in an office (18 m 2 , four individuals), and an apartment (110 m 2 , two individuals), was associated with a 2-4-fold increase in the concentration of airborne, culturable bacteria. A study of indoor air quality parameters in a lecture theatre in a Singapore school offers additional indirect evidence that the presence of occupants in classrooms may result in higher levels of bioaerosols.…”
Section: Introductionmentioning
confidence: 99%
“…2 Bacterial levels in a university office, auditorium, and apartments were found to be considerably elevated when people where present (925-1225 cfu m 23 occupied versus 92-182 cfu m 23 for unoccupied offices). 3 Endotoxin levels are higher in homes with animals. 4 However, recent studies of schools have not directly addressed the effect of occupancy on levels of bacteria or their constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Heavily occupied schools, factories, and offices, which often have limited air-flow due to modern air conditioning systems, represent a lesser but still substantial degree of contamination. [10][11][12][13][14][15] Environmental measurements of exposure to allergens, in dust samples, are routinely performed using individual enzyme immunoassays (ELISA) for each protein of interest. Antibodies are employed that target the most abundant allergens, whose source includes cats, dogs and dust mites.…”
Section: Discussionmentioning
confidence: 99%
“…7 Staphylococci, which are Gram positive bacteria, are among the most common organisms found on human skin, 8,9 and epithelial shedding with adherent bacteria might explain both chemical and physical observations. Others have also found increased microbial levels, 10,11 or particles [12][13][14][15][16] associated with occupation. In the current report, the first proteomic studies are described, to delineate human and environmental sources of dust present in indoor air.…”
Section: Introductionmentioning
confidence: 99%